Severan Books of Cassius Dio’s Roman History (LXXIV-LXXX) and their Byzantine Epitomators - Biały , Kamil (Studia Europaea Gnesnensia, 2018)
Severan Books of Cassius Dio’s Roman History (LXXIV-LXXX) and their Byzantine Epitomators